PENGARUH BERBAGAI MASA INKUBASI DAN DOSIS BOKASHI KOTORAN KAMBING TERHADAP PERTUMBUHAN BIBIT KETAPANG (Terminalia catappa L.) - Somba, Saron Melisa; Wardah, Wardah; Wulandari, Retno; Wahyuni, Dewi (Universitas Tadulako, 2021)
This study aims to determine the effect of goat manure bokashi with different incubation periods and dosages on the growth of ketapang (Terminalia catappa L.). This research factorial completely randomized design (CRD) method. The first factor is incubation period of bokashi (M) with 2 levels of treatment, namely M1 = incubation period of 1 week and M2 = incubation period of 2 weeks. The second factor is Bokashi (B) Dosage with 3 levels of treatment, namely B1 = Bokashi goat manure 200 g, B2 = Bokashi goat manure 400 g and B3 = Bokashi goat manure 800 g, from the six treatment levels each repeated nine times, so that the total unit of seedlings needed are 2 X 3 X 9 = 54 (fifty four) seedlings. The parameters observed were height (cm), diameter (cm) and leave numbers of seedlings. The results showed that the interaction between incubation period and goat manure bokashi dosage did not have a significant effect on the observation parameters, but for the treatment of goat manure bokashi with incubation period and bokashi dosage gave a significant effect on the observational parameters. Based on the least significant Test of 5%, it is known that the highest seedlings dimention was obtained in the treatment of the 2 weeks incubation period (M2) with an average of height increase of 10,8 cm, diameter of 3,2 mm and number of leaves of 18 sheets. For the bokashi dosage treatment, the highest results were obtained in the goat manure bokashi dosage treatment of 800 g (B3) with an average height increase of 8,5 cm, a diameter of 3,5 mm and a leaf number of 19 sheets.Keywords: ketapang, bokashi, goat manure, and incubation